ANALISIS PENGARUH SUKU BUNGA SBI DAN INFLASI TERHADAP PENGHIMPUNAN DANA PIHAK KETIGA (DPK) PERBANKAN DI INDONESIA - Herli Sopiana (Jurnal Ekonomi Pembangunan, 2012)
This research was aimed at identifying the influence of SBI's Rates and Inflation on Third-party Fund in Indonesia. It consisted of three variables: Third-party Fund, SBI's Rates, and inflation. It used secondary data published in reports of Bank Indonesia in the period of 1984. It used a quantitative multiple regression analysis and Autoregressive Moving Average (ARMA) approaches. The research result shows that the SBI's and Inflation simultaneously had a significant influence on Third-party Fund. The obtained R2 coefficient value was 0.944. It means that such influence reached 94% and the rest of 6% was influenced by other factors. The SBI's Rates had a positive influence on the third-party fund as shown by the coefficient of 0.651888. Conversely, the inflation had a negative influence on the Third party fund as shown by the coefficient of -0.2432. Keywords: third-party fund, SBI rates, inflation.